Estimation of Post-Mortem Interval Using Eye Organ in Animal Model Pigs - Albiruni Haryo; Rini Widayanti; Tri Wahyu Pangestiningsih; Aypbc Widyatmoko (The Indian Veterinary Journal, 2023)
In the process of death, a series of physical and chemical changes occur naturally and irreversibly, which will occur in each individual's body. This sequence of changes is mainly repetitive, although the speed with which they occur can vary significantly due to various factors caused by conditions in the field. In-depth understanding of the postmortem process and the factors influencing, it is crucial to know the Postmortem Interval (PMI) estimate. PMI estimation, also known as estimated time of death, to establish a timeline of events. Using the eye to obtain data that can be used as a method for determining the approximate post-mortem interval is one of the most accessible and efficient developments. For this purpose, the eye organ can be used as it is more resistant to postmortem changes. They are using variations in the concentration of potassium and glucose levels in the vitreous humor in the first 24 hours after death is achieved by observing body temperature data. The data were processed using multilinear regression analysis, resulting in a Summary Model R-sq (adj) of 98.76%, which means that the eye organ can be used to estimate mortality from early death in the 1-12 hour range.